Numerical Study of Savonius Wind Turbine Rotor with Elliptic Angle Shape Variation - Antonius Hadi Sudono Putranto; Vivien Suphandani Djanali; Bambang Arip Dwiyantoro (JMES The International Journal of Mechanical Engineering and Sciences, 2019)
The Savonius wind turbine uses a half-cylinder blade which is often called a bucket assembled so that the cross-section forms an "S". This turbine is seen in the form of a half-cylinder consisting of a concave side and a convex side. This turbine is one type of Vertical Axis Wind Turbine (VAWT) that uses the difference in drag forces between the two buckets to be able to rotate the rotor. Therefore this rotor has the ability to self-start, which other wind turbines do not have, even so, the performance of the turbine. Savonius wind is still relatively low, so that it cannot be applied until now. Many studies have been carried out to improve performance, some of which include adding shielding, end plates, changing the shape of the blades, gap overlap, and others. The analysis in this numerical study included a comparison of the performance of conventional Savonius wind turbines and elliptic Savonius wind turbines with an assumed steady flow 2D flow and using turbulent viscous transitions k-kL-ω and k-ω SST with variations in flow velocity and angle of incidence of flow to the position of the rotor of the Savonius turbine. This results evaluated were the static torque coefficient with respect to the rotor position, the pressure distribution along the blade surface, and the wind flow characteristics near the rotor. The results of this study indicated that the modified wind turbine rotor had a higher static torque coefficient at low speeds. The two types of turbine rotors had relatively the same self-starting capability at high speeds.